F-Box Protein Grr1 Interacts with Phosphorylated Targets via the Cationic Surface of Its Leucine-Rich Repeat - Hsiung, Yuchu G. (American Society for Microbiology, 2001)
The flexibility and specificity of ubiquitin-dependent proteolysis are mediated, in part, by the E3 ubiquitin ligases. One class of E3 enzymes, SKp1/cullin/F-box protein (SCF), derives its specificity from F-box proteins, a heterogeneous family of adapters for target protein recognition. Grr1, the F-box component of SCF(Grr1), mediates the interaction with phosphorylated forms of the G(1) cyclins Cln1 and Cln2. We show that binding of Cln2 by SCF(Grr1) was dependent upon its leucine-rich repeat (LRR) domain and its carboxy terminus. Our structural model for the Grr1 LRR predicted a high density of positive charge on the concave surface of the characteristic horseshoe structure. We hypothesized that specific basic residues on the predicted concave surface are important for recognition of phosphorylated Cln2. We show that point mutations that converted the basic residues on the concave surface but not those on the convex surface to neutral or acidic residues interfered with the capacity of Grr1 to bind to Cln2. The same mutations resulted in the stabilization of Cln2 and Gic2 and also in a spectrum of phenotypes characteristic of inactivation of GRR1, including hyperpolarization and enhancement of pseudohyphal growth. It was surprising that the same residues were not important for the role of Grr1 in nutrient-regulated transcription of HXT1 or AGP1. We concluded that the cationic nature of the concave surface of the Grr1 LRR is critical for the recognition of phosphorylated targets of SCF(Grr1) but that other properties of Grr1 are required for its other functions.